Effects of Plastic Covering on Yield, Physical and Chemical Characteristics of Some Table Grapes (Vitis vinifera L.) - COBAN, HARUN (Asian Journal of Chemistry, 2010)
This study was aimed to determine the effect of plastic covering on phenological stages (bud-burst, blooming, verasion, ripening) and the physical characteristics (the yield, cluster weight, cluster length, cluster width, berry weight, ber